1995
DOI: 10.1001/archsurg.1995.01430120068010
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response in Peritoneal Exudate and Plasma of Patients Undergoing Planned Relaparotomy for Severe Secondary Peritonitis

Abstract: Secondary peritonitis is associated with a significant cytokine-mediated inflammatory response that is compartmentalized in the peritoneal cavity and indicates an adverse prognosis. Levels of cytokines in the exudate of peritonitis may be used to better stratify the severity of peritonitis and, in future, to guide local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
63
3
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 32 publications
12
63
3
1
Order By: Relevance
“…If the host is healthy or bacteremia is not massive, it will be controlled without any other systemic repercussion. If, on the contrary, the host is jeopardized or bacteremia is very great, a systemic inflammatory response with commitment of the patient (sepsis) can be produced [16,17].…”
Section: Anatomy and Physiology Of The Peritoneummentioning
confidence: 99%
“…If the host is healthy or bacteremia is not massive, it will be controlled without any other systemic repercussion. If, on the contrary, the host is jeopardized or bacteremia is very great, a systemic inflammatory response with commitment of the patient (sepsis) can be produced [16,17].…”
Section: Anatomy and Physiology Of The Peritoneummentioning
confidence: 99%
“…It has been suggested that the low serum NT‐proCNP concentrations in dogs with SP may be explained by sequestration of NT‐proCNP in the abdominal cavity, such that NT‐proCNP concentration of abdominal fluid may provide a potential biomarker for the diagnosis of SP 4. This concept of compartmentalization has been previously described using other biomarkers in human patients with SP 8, 9. Indeed, human studies report higher cytokine concentrations including IL‐1, IL‐6, IL‐10, and TNF‐α in the abdominal fluid compared to plasma during SP 8, 9.…”
Section: Discussionmentioning
confidence: 90%
“…This concept of compartmentalization has been previously described using other biomarkers in human patients with SP 8, 9. Indeed, human studies report higher cytokine concentrations including IL‐1, IL‐6, IL‐10, and TNF‐α in the abdominal fluid compared to plasma during SP 8, 9. It has also been shown in rat models of sepsis‐induced peritonitis that accumulation of fibrin, leukocytes, and erythrocytes could obstruct the peritoneal stomata, thereby decreasing the peritoneal permeability and impairing the clearance of various intra‐abdominal cytokines 17…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations